2020
DOI: 10.1155/2020/1036306
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Influence of Selected Physical Factors on the Level of Pain in the Course of Temporomandibular Joint Disorders

Abstract: Introduction. Temporomandibular joints (TMJs) play a very significant function in the activity of the locomotor system of the masticatory system. But they are often a source of pain, myopathy, myoarthropathy, and malfunction of their surrounding or internal structures. The treatment of a patient’s discomfort associated with masticatory system dysfunctions strongly depends on their cause. Aim of the Study. The objective of the study was to evaluate the impact of selected physical factors: LED light therapy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…In the craniofacial area, the effectiveness of kinesiotaping in reducing swelling and pain was also found in more severe injuries as zygomatic–orbital fractures [ 38 ], mandibular fractures [ 39 ], and after orthognathic surgery [ 40 , 41 ]. It was also reported as effective in reducing the symptoms of chronical TMD [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the craniofacial area, the effectiveness of kinesiotaping in reducing swelling and pain was also found in more severe injuries as zygomatic–orbital fractures [ 38 ], mandibular fractures [ 39 ], and after orthognathic surgery [ 40 , 41 ]. It was also reported as effective in reducing the symptoms of chronical TMD [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,11,14,19,21,42 In addition to low-level laser therapy, several preclinical and clinical studies have suggested the application of light-emitting diodes (LEDs) for the treatment of various conditions involving acute nociceptive and chronic pain. 10,12,16,27,[30][31][32]40,[45][46][47]53 Although most studies have focused on the use of red and infrared light, few preclinical and clinical studies have explored the use of lower wavelength light. 22,33 In a rat model of acute nociceptive pain, green and to a lesser extent blue light (BL) exhibited thermal analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies that carried out trials of the application of EMF in the management of any pathology were developed in accordance with Declaration of Helsinki (Casalechi et al, 2020;Elshiwi et al, 2019;Mohajerani et al, 2019;Multanen et al, 2018) or endorsed by institution's ethics committee. Some studies used measurement scales to know the level of improvement in both pain, inflammation or disability of patients, such as visual analog scale (VAS) (Hattapoğlu et al, 2019;Kopacz et al, 2020), Western Ontario and McMaster Universities Osteoarthritis Index ( WOMAC) (Bagnato et al, 2016;Chen et al, 2019), Fibromyalgia Impact Questionnaire (FIQR) (Paolucci et al, 2016), Generalized Pain Index (WPI) (El Zohiery et al, 2021), Numerical Pain Rating Scale (NRS) (Abdulla et al, 2019;El Zohiery et al, 2021), Health Assessment Questionnaire (HAQ) (Paolucci et al, 2016) and American Spinal Injury Association (ASIA, Tarlov Scale (Ross et al, 2017). It is important to highlight that there were several modalities of EMF therapy approved by the Food and Drug Administration, where one of them was the PEMF, which is one of the most used therapies in the studies analyzed (Hu et al, 2020;Iwasa & Reddi 2018;Pesqueira et al, 2018;Ross et al, 2017;Vicenti et al, 2018).…”
Section: Resultsmentioning
confidence: 99%